"Start-up Nation" vs "the Republic of Samsung": power and politics in the partner choice discourse in Israeli–Korean business collaboration. Issue 2 (13th May 2021) - Lyan, Irina
Abstract : Purpose: This paper aims to propose to politicize partner choice as a discourse that rationalizes, legitimizes and justifies the choice of partners by underlining economic, cultural and institutional differences to (re)create power relations. By reconceptualizing partner choice as a discourse, the paper challenges the established view of partner choice according to international business and management studies as a rational and strategic behavior based on resource complementarity, best practices and win–win situations. Design/methodology/approach: Based on the longitudinal study of Israeli–Korean business collaboration, which includes in-depth interviews, observations and media texts, this paper uses critical discourse analysis (CDA) to demystify partner choice as neither a neutral nor an objective behavior to unveil its discursive construction and embeddedness in power relations. Findings: The actors on both sides of the Israeli–Korean business collaboration evoke resource complementary discourse between "Israeli innovation" and "Korean productivity" to rationalize their partner choice as a win–win situation. CDA demonstrates how both sides are engaged in a "borrowing" process from east-to-west and head-to-hands postcolonial images to (re)produce hierarchy between the parties. While east–west mapping remained almost unchallengeable, the reversal, crossing and blurring of the Israel-to-Korea knowledge transfer direction provides a counter-narrative to resource complementarity discourse. Originality/value: The resource complementarity discourse supported by east–west mapping and "head–hands" justifications for partner choice reveals the lingering presence of postcolonial images, imagery and imagination. By taking two nations without substantial troubled memories, histories and relations, the paper broadens the picture beyond national contexts, emphasizing the importance of borrowing and translation from postcolonial vocabulary to non-colonial situations.